Canonization, Morgan algorithm, equivalence classes - Meringer, Markus (Henry Stewart Talks, 2011)
Introduction: Why canonization?, Basic definitions: permutation, symmetric group, automorphism, Applications and implementations of canonizers, Morgan Algorithm, General strategies: initial classification, iterative refinement, labeling by backtracking, pruning the backtrack tree, profiting from symmetry, Symmetrically equivalent atoms, Outlook: equivalence classes of molecular graphs
Reviewed at 2020/08/05